2005
DOI: 10.1021/jf050952u
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Films Based on Chemically Cross-Linked Gliadins

Abstract: The aim of the present work has been to study the possibility of obtaining modified gliadin films with improved water resistance and mechanical properties by means of promoting intermolecular covalent bonds between polypeptide chains. Prior to casting films, formaldehyde, glutaraldehyde, and glyoxal were used to cross-link proteins at concentrations ranging from 1% to 4% (grams per 100 g of protein). Mechanical properties (tensile strength and elongation at break), water vapor permeability, moisture sorption i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
38
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 40 publications
7
38
0
Order By: Relevance
“…The dry film zein T g was not affected by the hydrogen peroxide treatments. This is in contrast to work which showed that covalent cross-linking substantially increased the T g of films cast from gliadin in the presence of cross-linking agents (Hernández-Muñoz et al, 2005). The absence of an effect of hydrogen peroxide treatment on zein T g is nevertheless consistent with the SDS-PAGE results (Fig.…”
Section: Zein Dough and Film Physico-chemical Propertiessupporting
confidence: 82%
“…The dry film zein T g was not affected by the hydrogen peroxide treatments. This is in contrast to work which showed that covalent cross-linking substantially increased the T g of films cast from gliadin in the presence of cross-linking agents (Hernández-Muñoz et al, 2005). The absence of an effect of hydrogen peroxide treatment on zein T g is nevertheless consistent with the SDS-PAGE results (Fig.…”
Section: Zein Dough and Film Physico-chemical Propertiessupporting
confidence: 82%
“…(9.9 ± 1.2 MPa) cinnamaldehyde were higher than those obtained for cross-linked gliadin films with 40% epichlorohydrin (6.5 ± 0.6 MPa) (Song et al, 2009), or 4% formaldehyde, glutaraldehyde or glyoxal (6.5 ± 0.7 MPa, 2.8 ± 0.8 MPa, and 2.1 ± 0.2 MPa respectively) (Hernandez-Munoz et al, 2005). The cross-linked films conditioned at 75% RH followed a similar pattern regarding σm and E parameters, but the great plasticization effect caused by water brought about a 2-fold reduction in the σm of these films with respect to those conditioned at 50% RH, and the E decreased dramatically, around 16-fold, compared to the cross-linked films conditioned at 50% RH.…”
Section: Mechanical Propertiesmentioning
confidence: 59%
“…In the case of gliadin films, various procedures have been employed in order to maximize their potential, including chemical cross-linking (Hernandez-Munoz et al, 2005;Hernandez-Munoz et al, 2004a;Hernandez-Munoz et al, 2004b;Hernandez-Munoz et al, 2004c;Reddy and Yang, 2010;Soares et al, 2009;Soares and Soldi, 2010;Song et al, 2009b), blends with other polymers (Li et al, 2010), and enzymatic cross-linking (Michon et al, 1999).…”
Section: Methods Of Production Referencesmentioning
confidence: 99%
See 2 more Smart Citations